2018
DOI: 10.3390/s18041113
|View full text |Cite
|
Sign up to set email alerts
|

3D-Subspace-Based Auto-Paired Azimuth Angle, Elevation Angle, and Range Estimation for 24G FMCW Radar with an L-Shaped Array

Abstract: In this paper, a three-dimensional (3D)-subspace-based azimuth angle, elevation angle, and range estimation method with auto-pairing is proposed for frequency-modulated continuous waveform (FMCW) radar with an L-shaped array. The proposed method is designed to exploit the 3D shift-invariant structure of the stacked Hankel snapshot matrix for auto-paired azimuth angle, elevation angle, and range estimation. The effectiveness of the proposed method is verified through a variety of experiments conducted in a cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It is found that the range and radial velocity of an object corresponds to the vertical and horizontal axis of the spectrum obtained by performing 2D FFT on a radar signal segment [9,10], which is usually referred to as the range-doppler spectrum. As shown for the ideal case in Fig.…”
Section: Preliminarymentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the range and radial velocity of an object corresponds to the vertical and horizontal axis of the spectrum obtained by performing 2D FFT on a radar signal segment [9,10], which is usually referred to as the range-doppler spectrum. As shown for the ideal case in Fig.…”
Section: Preliminarymentioning
confidence: 99%
“…In this work, we attempt to fully exploit the FWMC radar signals to detect the presence and estimate the 3D positions of objects based on DNNs. It is known that for an FWMC radar with multiple antenna receivers, 3D information (i.e., range, elevation and azimuth) of interested objects is embedded in the received radar signals [9,10]. Our motivation for exploiting the DNN-based approach is that radar signals can be preprocessed and treated as images.…”
Section: Introductionmentioning
confidence: 99%
“…In FMCW radar systems, to solve this problem of estimators based on FFT, subspace-based algorithms have been studied [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In [ 19 , 20 ], Estimation of Signal Parameters via Rotational Invariance Techniques (ESPRIT)-based algorithms are employed to accurately estimate the direction of arrival (DOA) of targets.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the algorithms of FMCW mmWave radar systems have been proposed [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Most of the proposed algorithms are based on Fast Fourier Transform (FFT), but it is difficult for FFT-based estimators to distinguish between two adjacent targets, such as ground and the water surface, because of the limitation of the bin width of the FFT spectrum given by , in which and , respectively, denote the sampling frequency and the number of samples [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although its resolution is higher than that of conventional FFT-based estimation algorithms, it is still a few centimeters without much improvement [ 24 ]. Other algorithms [ 25 , 26 , 27 , 28 , 29 , 30 ], such as the multiple signal classification (MUSIC) [ 27 ], and estimation of signal parameters via rotational invariance technique (ESPRIT) algorithms [ 29 ] are also proposed. However, those super-resolution algorithms all add too much computing complexity, which is opposed to the conception of edge computing.…”
Section: Introductionmentioning
confidence: 99%